Handbook of Industrial Chemistry and Biotechnology - Kent, James A.; Bommaraju, Tilak V.; Barnicki, Scott D. (Springer International Publishing : Imprint: Springer, 2017)
This widely respected and frequently consulted reference work provides a wealth of information and guidance on industrial chemistry and biotechnology. Industries covered span the spectrum from salt and soda ash to advanced dyes chemistry, the nuclear industry, the rapidly evolving biotechnology industry, and, most recently, electrochemical energy storage devices and fuel cell science and technology. Other topics of surpassing interest to the world at large are covered in chapters on fertilizers and food production, pesticide manufacture and use, and the principles of sustainable chemical practice, referred to as green chemistry. Finally, considerable space and attention in the Handbook are devoted to the subjects of safety and emergency preparedness. It is worth noting that virtually all of the chapters are written by individuals who are embedded in the industries whereof they write so knowledgeably.
Keywords: Chemistry.; Biotechnology.; Polymers.; Chemical engineering.; Quality control.; Reliability.; Industrial safety.; Pollution prevention.; elektronické knihy; electronic books